Economic and post - disaster in Gaza - Fares, Bissan Rajab; El Mougher, Mohammed M.; El Agha, Mohamed Ramadan (Journal of Risk and Crisis Management, 2019)
The Gaza Strip suffers from the economic destruction caused by the wars and siege, which constitutes a disaster for the Palestinian people. In this research, We discuss the role of the economy in the aftermath of the disaster and compare the State of Iraq in the face of its disaster and how it managed to get out of that crisis. There was an interview with Professor Naser Awad in the Ministry of Economy, On how to get out of the economic crisis in Gaza.
Keywords: Disaster; stages of disaster management; Ministry of economic; Reconstruction